Analysis of Factors Affecting the Effectiveness of Road Maintenance in Pidie Regency - Yanis, Muhammad; Hamzani, Hamzani; Alkhaly, Yulius Rief (International Journal of Engineering, Science and Information Technology, 2024)
Land transportation infrastructure as a medium of accessibility for various community needs that have an important role in economic growth, socio-cultural, political, and other factors of a region or area. In order for road infrastructure to function optimally in improving these factors, several important aspects need to be considered, including having user safety and comfort, environmentally friendly. Land transportation infrastructure is not only a means of mobility but also a tool to achieve better social and economic welfare for the entire community. Given the strategic role of land transportation infrastructure, namely roads, it is very necessary to have security and comfort values so that the efficiency and effectiveness of the infrastructure are indicators to be evaluated. The effectiveness and efficiency of roads are greatly influenced by many factors including road conditions and age, land use, social, economic and policy. community and related parties. The purpose of this study is to analyze the dominant factors that influence the effectiveness of road maintenance in Pidie district. This study uses a qualitative approach to analyze data obtained from respondents which are primary data and the use of SPSS as an analysis tool so that it becomes numerical. The results obtained for the instrument items used are reliable and trustworthy, this is based on the Cronbach's Alpha (CA) value obtained in the range of 0.50 to 0.70. Based on the results and discussions obtained, it can be concluded that all proposed instrument items provide a significant contribution to determining the effectiveness of road maintenance decisions in Pidie Regency with the highest influence instrument factors being economic instruments and road conditions. The coefficient value obtained for the two factors is 5.571 for the economic instrument and followed in second place, namely the road condition instrument item with a coefficient of 3.603.